2010
DOI: 10.3390/f1040209
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Climate on the Growth of Hybrid Poplar in Michigan

Abstract: This study examined the influence of climate on cumulative and interannual growth patterns of 18 full-sib families of hybrid poplars (Populus × smithii Boivin) derived from different geographical locations (state counties) of natural stands of aspen parents (trembling aspen (Populus tremuloides Michx.) and bigtooth aspen (Populus grandidentata Michx.)). The hybrids were subsequently planted in 1982 in southern midMichigan at Michigan State University (MSU) Sandhill Research Area. Cumulative measures of hybrid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Climate variability drives forest productivity and tree growth [1][2][3]. The implications of forecasted warmer and drier conditions become crucial to predicting forest productivity in Northern Mexico where the frequency of severe drought is expected to increase [4].…”
Section: Introductionmentioning
confidence: 99%
“…Climate variability drives forest productivity and tree growth [1][2][3]. The implications of forecasted warmer and drier conditions become crucial to predicting forest productivity in Northern Mexico where the frequency of severe drought is expected to increase [4].…”
Section: Introductionmentioning
confidence: 99%
“…Water deficit has been reported as one of the major triggering factors of forest growth decline, dieback, and tree mortality [3][4][5]. Droughts reduce radial growth and alter the hydraulic conductivity of trees [6][7][8], with a negative impact on carbon sequestration [9,10] and forest productivity [11,12]. Moreover, given that aridity is expected to intensify in the future in many forested areas, this may have negative and long-term implications on forest productivity [7,13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the usefulness of dendrochronological methods for observing the impacts of climate, disturbance events, insects and diseases on radial growth [40,48,49]. In dendrochronology, valid inferences can be made indirectly about the mechanisms of tree response to their environment [50].…”
Section: Dendrochronologymentioning
confidence: 99%